The effect of intraovarian injection of platelet-rich plasma on ovarian morphology and insulin resistance in polycystic ovary syndrome (PCOS) rats - Mojtaba Sarvestani; Alireza Rajabzadeh; Gholamreza Ghavipanjeh; Tahereh Mazoochi; Morteza Salimian (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Polycystic ovary syndrome (PCOS) is a multifaceted endocrine and infertility disorder characterized by symptoms such as insulin resistance, hyperandrogenism, anovulation, and ovarian cysts. This study aimed to examine the effect of intraovarian injection of platelet-rich plasma (PRP) on ovarian morphology and insulin resistance in a PCOS rat model. Methods: In this experimental study, 20 Wistar rats were divided into four groups (N=5): control, sham, PCOS, and PCOS group treated with PRP. PCOS was induced using 1 mg/kg of letrozole dissolved in 0.5% carboxymethyl cellulose. The PRP group received 35 microliters of PRP injected directly into both ovaries. After 14 days of treatment, serum insulin levels, blood glucose, and the insulin resistance index (HOMA-IR) were measured. Ovarian tissue sections were also examined for histopathological changes and follicle count. Results: Intraovarian injection of PRP led to a significant decrease in serum insulin levels (P<0.01) and glucose levels (P<0.01) compared to the PCOS group. The PRP-treated groups exhibited a significant reduction in the insulin resistance index (HOMA-IR) (P<0.0001). Histological analysis demonstrated that a single dose of PRP improved the ovarian pathological condition, resulting in a significant increase in healthy follicles at all developmental stages and corpus luteum (P<0.0001), along with a significant decrease in cystic follicles (P<0.0001). Conclusion: Intraovarian PRP injection may ameliorate PCOS symptoms, including ovarian morphology and insulin resistance. However, further studies are necessary to elucidate the underlying mechanisms of PRP's effectiveness.